An Employees Attendance Management System with QR Code - Deebana a/p Kanthi Perumal (Applied Information Technology And Computer Science, 2023)
Attendance tracking is a tiring and time-consuming task. Each day, the same procedure for taking attendance will be implemented. Although there are electronic presence systems on the market, there are still large companies that have not yet applied them. At The Store Sdn Bhd, a well-known supermarket company still uses traditional and non -automated methods. It requires many manual workers to manage attendance data as it is directly related to the payroll system. Thus, automated attendance systems can reduce human labor and improve attendance recruitment efficiency. The goal of this project is to automate attendance tracking. Evolutionary prototypes are used as a guide to system development. This proposed system is used by the Human Resourcer and the employees. There are six modules in this system, that includes Registration and Login Module where it might manage a new user registration and login details. The next module is Employee Profile Module, which will be managed by the HR to manage the list of employees, view, search or update the employee details. The Mark Attendance Module is important where it will allow the employee to enroll their attendance with the QR Code. The HR might supervise the attendance information and details in the Attendance Management Module. The salary module is used to reveal the salary of the employees. The reporting module helps to generate the report of the employee’s attendance. This system was developed by using PHP language and was based on Object Oriented software Development (OOSD) methodology. This strategy can save time for administrators when controlling attendance, make it easier for employees to register attendance, and lessen the possibility of inaccurate records